Lacustrine mass movements in active tectonic settings: Lake tsunami sources in New Zealand's South Island - Katie E. Hughes; Sean J. Fitzsimons; Jamie D. Howarth (Geomorphology, 2024)

Sedimentary ancient DNA reveals the impact of anthropogenic land use disturbance and ecological shifts on fish community structure in small lowland lake - Georgia Thomson-Laing; Jamie D. Howarth; Javier Atalah; Marcus J. Vandergoes; Xun Li; John K. Pearman; Sean Fitzsimons; Chris Moy; Adelaine Moody; Claire Shepherd; Nicholas McKay; Susanna A. Wood (Science of The Total Environment, 2024)

Subglacial deformation of permafrost beneath Wright Lower Glacier, Antarctica as revealed by direct observations and measurements from a subglacial tunnel - Sean Fitzsimons; Martin Sharp; Reginald Lorrain (Geomorphology, 2023)

Turning a lost reef ecosystem into a national restoration program - Dominic McAfee; Ian M. McLeod; Heidi K. Alleway; Melanie J. Bishop; Simon Branigan; Sean D. Connell; Craig Copeland; Christine M. Crawford; Ben K. Diggles; James A. Fitzsimons; Ben L. Gilby; Paul Hamer; et al. (Conservation Biology, 2022)
Achieving a sustainable socioecological future now requires large‐scale environmental repair across legislative borders. Yet, enabling large‐scale conservation is complicated by policy‐making processes that are disconnected from socioeconomic interests, multiple sources of knowledge, and differing applications of policy. We considered how a multidisciplinary approach to marine habitat restoration generated the scientific evidence base, community support, and funding needed to begin the restoration of a forgotten, functionally extinct shellfish reef ecosystem. The key actors came together as a multidisciplinary community of researchers, conservation practitioners, recreational fisher communities, and government bodies that collaborated across sectors to rediscover Australia's lost shellfish reefs and communicate the value of its restoration. Actions undertaken to build a case for large‐scale marine restoration included synthesizing current knowledge on Australian shellfish reefs and their historical decline, using this history to tell a compelling story to spark public and political interest, integrating restoration into government policy, and rallying local support through community engagement. Clearly articulating the social, economic, and environmental business case for restoration led to state and national funding for reef restoration to meet diverse sustainability goals (e.g., enhanced biodiversity and fisheries productivity) and socioeconomic goals (e.g., job creation and recreational opportunities). A key lesson learned was the importance of aligning project goals with public and industry interests so that projects could address multiple political obligations. This process culminated in Australia's largest marine restoration initiative and shows that solutions for large‐scale ecosystem repair can rapidly occur when socially valued science acts on political opportunities.

Lake microbial communities are not resistant or resilient to repeated large‐scale natural pulse disturbances - Katie A. Brasell; Jamie Howarth; John K. Pearman; Sean J. Fitzsimons; Anastasija Zaiko; Xavier Pochon; Marcus J. Vandergoes; Kevin S. Simon; Susanna A. Wood (Molecular Ecology, 2021)
Opportunities to study community‐level responses to extreme natural pulse disturbances in unaltered ecosystems are rare. Lake sediment records that span thousands of years can contain well‐resolved sediment pulses, triggered by earthquakes. These palaeorecords provide a means to study repeated pulse disturbances and processes of resistance (insensitivity to disturbance) and ecological resilience (capacity to regain structure, function and process). In this study, sedimentary DNA was extracted from a sediment core from Lake Paringa (New Zealand) that is situated in a near natural catchment. Metabarcoding and inferred functions were used to assess the lake microbial community over the past 1100 years – a period that included four major earthquakes. Microbial community composition and function differed significantly between highly perturbed (postseismic, ~50 years) phases directly after the earthquakes and more stable (interseismic, ~250 years) phases, indicating a lack of community resistance. Although community structure differed significantly in successive postseismic phases, function did not, suggesting potential functional redundancy. Significant differences in composition and function in successive interseismic phases demonstrate that communities are not resilient to large‐scale natural pulse disturbances. The clear difference in structure and function, and high number of indicator taxa (responsible for driving differences in communities between phases) in the fourth interseismic phase probably represents a regime shift, possibly due to the two‐fold increase in sediment and terrestrial biospheric organic carbon fluxes recorded following the fourth earthquake. Large pulse disturbances that enhance sediment inputs into lake systems may produce an underappreciated mechanism that destabilises lake ecosystem processes.

Processes of distribution of pharmaceuticals in surface freshwaters: implications for risk assessment - Simone Bagnis; Mark F. Fitzsimons; Jason Snape; Alan Tappin; Sean Comber (Environmental Chemistry Letters, 2018)

A hydroclimate-proxy model based on sedimentary facies in an annually laminated sequence from Lake Ohau, South Island, New Zealand - Heidi A. Roop; Richard Levy; Gavin B. Dunbar; Marcus J. Vandergoes; Jamie Howarth; Sean Fitzsimons; Heung Soo Moon; Christian Zammit; Robert Ditchburn; Troy Baisden; Ho Il Yoon (Journal of Paleolimnology, 2016)

Rotating micro-structures in Antarctic cold basal ice: implications for glacier flow and its interpretation - Denis Samyn; Sean J. Fitzsimons; Reginald D. Lorrain (International Journal of Earth Sciences, 2010)